Metabolic programming of obesity by energy restriction during the perinatal period: different outcomes depending on gender and period, type and severity of restriction - Pico, Catalina; Palou, Mariona; Priego, Teresa; Sanchez, Juana; Palou, Andreu (Frontiers in Physiology, 2012)
Epidemiological studies in humans and controlled intervention studies in animals have shown that nutritional programming in early periods of life is a phenomenon that affects metabolic and physiological functions throughout life. The phenotypes of health or disease are hence the result of the interaction between genetic and environmental factors, starting right from conception. In this sense, gestation and lactation are disclosed as critical periods. Continuous food restriction during these stages may lead to permanent adaptations with lasting effects on the metabolism of the offspring and may influence the propensity to develop different chronic diseases associated with obesity. However, the different outcomes of these adaptations on later health may depend on factors such as the type, duration, period and severity of the exposure to energy restriction conditions, and they are, in part, gender specific. A better understanding of the factors and mechanisms involved in metabolic programming, and their effects, may contribute significantly to the prevention of obesity, which is considered to be one of the major health concerns of our time. Here, the different outcomes of maternal food restriction during gestation and lactation in the metabolic health of offspring, as well as potential mechanisms underlying these effects are reviewed.